2005
DOI: 10.1007/s00203-005-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a gene cluster for dibenzofuran degradation in a new dibenzofuran-utilizing bacterium, Paenibacillus sp. strain YK5

Abstract: Spore-forming bacterial strains capable of utilizing dibenzofuran (DF) as a sole source of carbon and energy were isolated. Characteristics of the isolates justified their classification into the genus Paenibacillus, and their closest relative was P. naphthalenovorans. Degenerate primers for aromatic hydrocarbon dioxygenase alpha subunit (AhDOa) genes and genomic DNA of the strain YK5 were used for gene isolation. The nucleotide sequences of clones of the PCR products revealed that the strain YK5 carries at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…The procedures used for isolation of genomic DNA, plasmid DNA, and total RNA of bacterial strains and the procedures used for Southern and Northern hybridization analyses have been described previously (20)(21)(22). PCR amplification was carried out using ExTaq DNA polymerase (TAKARA BIO, Shiga, Japan) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedures used for isolation of genomic DNA, plasmid DNA, and total RNA of bacterial strains and the procedures used for Southern and Northern hybridization analyses have been described previously (20)(21)(22). PCR amplification was carried out using ExTaq DNA polymerase (TAKARA BIO, Shiga, Japan) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a transcriptional regulation system for genes derived from DBF63, YK3, and YK5 has been demonstrated. Transcription of the dfdA1 and dbfA1 YK5 genes was induced in strains YK3 and YK5, respectively, by cultivation with DF (20,22). In contrast, tran-scription of the dbfA1 DBF63 gene was induced not only by DF but also by fluorene (36), and it was subsequently demonstrated that the dbfA1A2 genes are linked to the fluorenephthalate catabolic gene cluster (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorinated dioxins were quantified in three individual extracts of each substrate with GC-MS, as described previously. 32) Substrates extracted from the resting cell cultures of RD2 transformed with vector plasmid pRK401 were used as negative control. The substrate depletion rates were calculated by comparing the amount of substrate remaining in the AhDO-expressed resting cell cultures, the mean being the amount of substrate remaining in the negative control.…”
Section: Fig 1 Structures Of Ahdo-expression Constructs Used In Thismentioning
confidence: 99%